2000
DOI: 10.1017/s0021963099005284
|View full text |Cite
|
Sign up to set email alerts
|

Precursors of Literacy Delay among Children at Genetic Risk of Dyslexia

Abstract: This paper reports the literacy skills of 63 children selected as being at genetic risk of dyslexia compared with 34 children from families reporting no history of reading impairment. Fifty-seven per cent of the at-risk group were delayed in literacy development at 6 years compared with only 12% of controls. The "unimpaired" at-risk group were not statistically different from controls on most cognitive and language measures at 45 months, whereas the literacy-delayed group showed significantly slower speech and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

29
204
0
16

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 287 publications
(249 citation statements)
references
References 0 publications
29
204
0
16
Order By: Relevance
“…Converging evidence has since been reported by several studies of children at high risk of dyslexia before formal schooling begins (Byrne, Fielding-Barnsley, Ashley, & Larsen, 1997;Gallagher, Frith, & Snowling, 2000;Locke et al, 1997;Lyytinen, Poikkeus, Laakso, Eklund, & Lyytinen, 2001;Lefly & Pennington 1996). However, it needs to be borne in mind that this method of recruitment is very different from that used in more conventional group studies that have selected children who fulfill ÔdiscrepancyÕ and other more conventional criteria for reading disability.…”
Section: Dyslexia Across the Life-spanmentioning
confidence: 86%
“…Converging evidence has since been reported by several studies of children at high risk of dyslexia before formal schooling begins (Byrne, Fielding-Barnsley, Ashley, & Larsen, 1997;Gallagher, Frith, & Snowling, 2000;Locke et al, 1997;Lyytinen, Poikkeus, Laakso, Eklund, & Lyytinen, 2001;Lefly & Pennington 1996). However, it needs to be borne in mind that this method of recruitment is very different from that used in more conventional group studies that have selected children who fulfill ÔdiscrepancyÕ and other more conventional criteria for reading disability.…”
Section: Dyslexia Across the Life-spanmentioning
confidence: 86%
“…Two critical dimensions that may be important are the degree of phonological deficit and the degree of language impairment (Gallagher, Frith, & Snowling, 2000;Griffiths & Snowling, 2002;Joanisse et al, 2000;Manis, Seidenberg, Doi, McBride-Chang, & Petersen, 1996;Stanovich, Siegel, & Gottardo, 1997). According to the phonological representations hypothesis, the degree of phonological impairment should be the primary variable affecting gating task performance.…”
Section: Introductionmentioning
confidence: 99%
“…Phonological processing skills have been found to be a key predictor of later reading ability in preschool and elementary schoolaged children (19-31). In addition to phonological processing deficits, a range of other linguistic impairments have been observed in infants and prereading children who later exhibit weak reading scores, including speech perception (23, 26), syntax production, and comprehension (32-35), language comprehension (26), receptive vocabulary (22,34), and rapid automatized naming abilities (23,24,34,(36)(37)(38).With the advent of modern neuroimaging tools, it is now possible to study the neural substrates of reading and reading-related processes in the conscious human brain. Functional MRI (fMRI) studies have revealed a characteristic network of posterior brain areas typically involved in reading and reading-related tasks in children and adults including: (i) the dorsal or temporoparietal circuit (including lateral extrastriate and left inferior occipital areas) and (ii) the ventral or occipitotemporal circuit [including angular and supramarginal gyrus, inferior parietal lobe, and posterior aspects of the superior temporal gyrus (39-43)].…”
mentioning
confidence: 99%
“…Phonological processing skills have been found to be a key predictor of later reading ability in preschool and elementary schoolaged children (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). In addition to phonological processing deficits, a range of other linguistic impairments have been observed in infants and prereading children who later exhibit weak reading scores, including speech perception (23,26), syntax production, and comprehension (32)(33)(34)(35), language comprehension (26), receptive vocabulary (22,34), and rapid automatized naming abilities (23,24,34,(36)(37)(38).…”
mentioning
confidence: 99%